Autophagy and proinflammatory cytokines: Interactions and clinical implications. (October 2018) - Ge, Yun; Huang, Man; Yao, Yong-ming
Graphical abstract: Highlights: Autophagy is induced by interferon (IFN)-γ, interleukin (IL)-1, tumor necrosis factor (TNF)-α, IL-17, and IL-6, whereas the process is blocked by IL-13, IL-33, IL-10, and IL-4. Autophagy facilitates the production of IFN-γ, TNF-α, IL-1β and inhibits the secretion of TNF-α, IL-17, IL-1β, IL-α. Autophagy is a promising target for developing novel therapeutic strategies against inflammatory and infectious diseases. TNF-α, IL-1β, and IFN-γ promote autophagy and prevent pathogen invasion; Moreover, IFN-γ can promote the generation of immunity in diseases involving immunosuppression. On the other hand, TNF-α, IL-1β, or IL-17 can trigger excessive autophagy, which contributes to the pathophysiology of several diseases. Abstract: Autophagy is a ubiquitous cellular process that regulates cell growth, survival, development and death. Its process is closely associated with diverse conditions, such as liver diseases, neurodegenerative diseases, myopathy, heart diseases, cancer, immunization, and inflammatory diseases. Thus, understanding the modulation of autophagy may provide novel insight into potential therapeutic targets. Autophagy is closely intertwined with inflammatory and immune responses, and cytokines may help mediate this interaction. Autophagy has been shown to regulate, and be regulated by, a wide range of proinflammatory cytokines. This review aims to summarize recent progress in elucidating the interplay between autophagy and proinflammatory cytokines, including IFN-γ, TNF-α, IL-17, and cytokines of the IL-1 family (e.g., IL-1α, IL-1β, IL-33, and IL-36).